Four varieties of diabetes mellitus in acute myocardial infarction - Koraćević Goran; Obradović Slobodan; Kostić Tomislav; Pavlović Milan; Kutlešić Marija; Stojanović Milovan; Vasiljević Slađana; Koraćević Maja (Vojnosanitetski Pregled)
nema